Contributions to the knowledge of the "Staphylinus-complex" (Coleoptera: Staphylinidae: Staphylinini) of China. Part 7. The genus Sphaerobulbus Smetana 2003. Section 2 - Smetana, Aleš (Zootaxa, 2005)
This is the second paper dealing with the Chinese species of the genus Sphaerobulbus Smetana, 2003. Four species are described as new: S. rex (Shaanxi), S. pusio (Sichuan), S. businskorum (Sichuan) and S. bicolor (Sichuan). Notes concerning the taxonomy of S. bisinuatus Smetana, 2003 and S. abdominalis Smetana, 2003 are presented. New distributional records for S. bisinuatus, S. brezinai Smetana, 2003, S. yulongmontis and S. murzini Smetana, 2003 are given.